Confined Nano‐NMR Spectroscopy Using NV Centers. Issue 11 (15th June 2020) - Cohen, D.; Nigmatullin, R.; Eldar, M.; Retzker, A.
Abstract: Nano nuclear magnetic resonance (nano‐NMR) spectroscopy with nitrogen‐vacancy (NV) centers holds the potential to provide high‐resolution spectra of minute samples. This is likely to have important implications for chemistry, medicine, and pharmaceutical engineering. One of the main hurdles facing the technology is that diffusion of unpolarized liquid samples broadens the spectral lines thus limiting resolution. Experiments in the field are therefore impeded by the efforts involved in achieving high polarization of the sample which is a challenging endeavor. Here, a scenario where the liquid is confined to a small volume is examined. It is shown that the confinement "counteracts" the effect of diffusion, thus overcoming a major obstacle to the resolving abilities of the NV‐NMR spectrometer. Abstract : Nano‐scale nuclear magnetic resonance spectroscopy holds the promise to outperform microscopy. The measurement of the spectrum of liquid samples is especially challenging since the self‐diffusion of the liquid broadens the spectral lines. Recently, the NV community has started working on utilizing confinement to limit this broadening. Here, the theoretical foundation required for the performance and analysis of such experiments is provided.